Do Project Management Determine Successful Completion of Projects? A Study of Indonesian Contractors - Aris Subagio; Rachmat Mudiyono; Sumirin Sumirin (Pondasi, 2022)
AbstractFor a successful execution of construction projects, project owners and contractors need for a good management system capable of monitoring and evaluating progress of the project. By employing a descriptive quantitative method, this study aimed to explore project management components used by contractors in the city of Kudus, Central Java Indonesia and to find out its relation to successful completion of their projects and determine the most dominant component in the management. Data for the study were in the form of numbers collected from 100 respondents through survey. Finding of the study were then quantitatively analyzed based on our pre-determined criteria. Our findings showed successful completion of projects was very much determined by the quality of project management, including planning, organizing, actuating and controlling. Among those four components of management, organization was the most dominant aspect to influence successful execution of a project. Role of organization in the project was critical to coordinate parties by which they were enabled to supervise, optimize specialization, efficiently use the budget and build harmonious relationship among parties.Keyword: Management, Contractor, Work Quality